Umfrage: Ein Jahr Corona-Krise aus Sicht der Selbstständigen; Survey: One Year into the COVID-19 Crisis - Views of the Self-employed - Caroline Stiel; Alexander Kritikos; Jörn Block; Irene Bertschek (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
In spring 2021, DIW Berlin, ZEW Mannheim, and the University of Trier conducted an online survey among self-employed persons to collect data about the situation of the self-employed in Germany one year after the beginning of the COVID-19 pandemic. The online survey was disseminated in cooperation with the Verband der Gründer und Selbstständigen Deutschland (VGSD) e.V. and other professional associations. The questionnaire includes 58 questions and focuses on the following topics: impact of the pandemic on the venture, financial situation during the pandemic, application for government support programs, business strategies to overcome the crisis, assessments of the future, well-being, and sociodemographic and business-related characteristics.
Keywords: 330; self-employed; COVID-19 pandemic; Germany; entrepreneurship; economic crisis; financial aid